Optimilisasi distribusi sembako oleh baznas kota blitar untuk fakir dhuafa di tiga kecamatan - Wicaksono, Naufal Rizki; Wardana, Guntur Kusuma (Maliki Interdisciplinary Journal, 2025)
The optimization of food package distribution is a strategic initiative by BAZNAS Kota Blitar to support the welfare of the underprivileged. This study aims to analyze the effectiveness of the food distribution program in three districts—Kepanjen Kidul, Sukorejo, and Sananwetan—and identify challenges in its implementation. A qualitative descriptive method was used, with data collected through observation, interviews, and documentation from official BAZNAS reports. The findings indicate that the distribution system is based on social data, in collaboration with local government and community leaders, while prioritizing transparency in zakat fund management. The program successfully reached over 1,000 beneficiaries and had a positive impact on alleviating their economic burdens. However, challenges remain, such as limited resources and the need for innovation in distribution methods to ensure greater equity and efficiency. Therefore, strengthening distribution strategies, including utilizing digital technology to enhance data accuracy and distribution effectiveness, is crucial. With continuous optimization, this program can serve as a model for other regions in maximizing the role of zakat in improving social welfare.